Swaziland Solar Electrification Program 2001-2010 : Phase 1. 2001-2002 Solar Energy in the Pilot Area - World Bank (Washington, DC, 2014)
The report presents the solar electrification program in Swaziland, aimed at meeting the basic electrical needs of rural communities, of which currently, less than five percent is connected to power grids. Although implementation efforts have been made towards the development of sustainable solar markets in the country, a number of constraints, and barriers hinder implementation, e.g., rigid product assortment, focused on photovoltaic technology, rather than service delivery, and, aggravated by poor access to credit. The initial step, creation of awareness will play a pivotal role, since acceptance of solar electrification by the rural community, the government, and the electricity utility Swaziland Electricity Board (SEC), is critical to the sustainability of the program. The deliverables of this solar electrification program include: basic needs assessment, focused on energy needs for both productive, and community activities; development, and implementation of a wide range of solar products, delivery modes, and promotion strategies; monitoring, and evaluation of solar energy uptake, energy use, energy expenditures, and user satisfaction, compared with baseline conditions; and, continued efforts to prod, at a national level, the enactment of a rural electrification policy.